A Business perspective of the United States Tennis Association's American Development Model: discover, develop, play - Davies, Karl; Roetert, E.Paul (ITF Coaching & Sport Science Review, 2023)
The American Development Model (ADM) implemented by the United States Tennis Association (USTA) has gained significant attention for its player-centric approach and structured framework. While previous studies have explored the impact of the ADM on player development, this approach takes a unique business perspective to analyze the model's efficacy and implications. Drawing upon business management theories and practices, this overview examines the ADM's alignment with strategic planning, resource allocation, talent acquisition, and marketing within the context of the USTA. This article sheds light on the business strategies employed by the USTA in implementing the ADM, highlighting potential areas for improvement, and providing practical recommendations for other National Governing Bodies of sport seeking to adopt similar player development models. Overall, this information contributes to the existing literature by bridging the gap between sports management and player development approaches, providing a more comprehensive understanding of the ADM from a business standpoint.